A study on the cement-based decorative materials in the San Fedele Church in Milan. (December 2017) - Lollini, Federica; Carsana, Maddalena; Bertolini, Luca
Abstract: Cement-based materials have been used since the 19th century for different decorative purposes, and a high levels of expertise has often reached in reproducing or restoring even quite elaborated stoneworks. An important example is the application of cement-based decorative materials on the façades of the San Fedele church in Milan. The church, built in the 16th century and characterized by the presence of pinkish-yellowish Angera stone on the façades, was subjected, especially in the 20th century, to several restoration works. Damaged decorative elements of the façades as well as portions of its structural elements were replaced or covered in the last century by "stone imitating render", made with cementitious materials which imitate the original Angera stone. In this study, several samples of cement-based decorative materials, collected from different elements of the external façades of the Church, were characterized by several analytic techniques (thermogravimetric analysis, X-ray diffraction, scanning electron microscopy and IR analysis), in order to investigate both their microstructure and composition, how the chromatic aspect of the cementitious materials were obtained and their conservation state and to provide useful information for the possible reproduction of materials with comparable appearance to be used in a further restoration project. Results showed that the cement-based materials and decorations were obtained by the application of different layers of renders; in particular, the colour and texture of finishing layer were achieved by blending the binder with fine dolomite particles, probably obtained by grinding the Angera stone. This technique not only allowed an amazing reproduction of the original stone, but also resulted in a durable protection, since the cement-based decorative materials did not show any significant degradation phenomena in the polluted environment of the centre of Milan.